Examen especial a la cuenta préstamos vencidos microcréditos de 91 a 180 días de la Cooperativa de Ahorro y Crédito 29 de octubre ltda.” Periodo: octubre-diciembre/ 2012 - Campoverde Vásquez, Ana Belén (2016)
The present thesis of investigation denominated Special "Exam to The Bill Conquered Loans Microcredits of 91 to 180 Days of the Cooperative of Saving and Credit October 29 Ltda. Period October - December of the 2012 it was carried out to complete a prerequisite to the obtaining of the Title of Engineer in Accounting and Audit CPA, in the National University of Loja, their development was held to the Organic Law of the Popular and Solidary Economy and of the Popular and Solidary Financial Sector, Countable Principles, Regulation of Credit, Organic Law for the Institutions of the Financial System. The objective was to carry out a special exam to the bill Conquered Loans Microcreditors from 91 to 180 Days of the Cooperative of Saving and Credit October 29 Ltda. Period October - December of the 2012, for the execution of the same one the system of internal control was evaluated to the carried out credit obligations, you verifies the documentation source with the requirements settled down in the credit regulation, you could also apply the three phases of the special exam the same ones that us to help to obtain enough, competent and pertinent information of the examined item stops then to conclude with the report of the special exam the same one that will contain comments, conclusions and recommendations. With the culmination of the special exam, you concludes that the Cooperative of Saving and Credit incomplete with the countable norms, and other applicable legal dispositions for the internal control of the granted credits, reflecting a credit linking bearing that he/she has a high credit risk the Cooperative.